Naive Images of Globalization from a Linguistic Viewpoint - Skrebtsova, Tatyana G. (Respectus Philologicus, 2003)
The notion of globalisation is gaining ground in modern world but its meaning is still rather vague and uncertain. Scholars make their best trying to provide this new phenomenon with an expert definition and thus fit it into the scientific worldview. Globalisation is also widely discussed in the media and enjoys lively interest on the part of laymen. People try to grasp it, form their opinion and attitude toward it. The resulting images of globalisation in popular mind differ greatly, with attitudes ranging from extremely negative to moderately favourable.The paper presents an analysis of naive views of globalisation based on cognitive linguistics methodology and, in particular, on conceptual metaphor theory of G. Lakoff and M. Johnson. Research data are drawn from Russian-language Internet resources. The paper investigates conceptual metaphors that contribute to the naive understanding of the phenomenon. Two major images of globalization in popular mind are singled out and examined.
Keywords: cognitive linguistics; conceptual metaphor theory; sprachliches Weltbild; mental representation